STANDAR KEBUTUHAN DAN UKURAN RUANG RUMAH MIKRO UNTUK GENERASI Z DI KOTA PONTIANAK - Maro, Aimee Amelia; Kalsum, Emilya; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2025)
Population growth is influenced by birth and death rates, along with economic development and urbanization. Population growth leads to increased needs for clothing, food, and shelter. Urbanization influences society to become more modern and influences aspects of life such as lifestyle and consumption preferences. This makes the increasing need for housing in the form of housing need to be adjusted to the characteristics of today's society. This study aims to identify the needs and size of micro-houses based on the preferences of generation Z in Pontianak City. The study used a qualitative approach with descriptive statistical analysis methods on questionnaire data. The results show that generation Z's space needs are strongly influenced by daily activities such as sleeping, eating, bathing, and special activities such as working, studying, and hobbies. Micro-houses for generation Z in Pontianak City are not only used to fulfill biological needs. They have a multitasking lifestyle, accustomed to working from home with the use of technology, so they require spaces with productive functions. The spaces they need are a living room, family room, master bedroom, children's bedroom, dining room, kitchen, bathroom, hobby room, work room, laundry room, and storage. The analysis results show that houses with sizes of ±22 to ±36 can meet all the needs of generation Z if arranged efficiently. Keywords: Space Requirements, Room Size, Micro House, Generation Z